2019
DOI: 10.3390/biom9050192
|View full text |Cite
|
Sign up to set email alerts
|

Relative Telomere Length and Cardiovascular Risk Factors

Abstract: (1) Background: Telomeres are repetitive DNA sequences located at the extremities of chromosomes that maintain genetic stability. Telomere biology is relevant to several human disorders and diseases, specifically cardiovascular disease. To better understand the link between cardiovascular disease and telomere length, we studied the effect of relative telomere length (RTL) on cardiovascular risk factors in a large population-based sample. (2) Methods: RTL was measured by a real-time quantitative polymerase chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 36 publications
0
9
0
1
Order By: Relevance
“…Previous studies have reached inconsistent conclusions on the correlation between TL and hypertension. For instance, some previous studies suggested that there was no association between TL and blood pressure ( 38 40 ). A previous meta-analysis of 10 studies indicated a significant negative correlation between TL and hypertension ( 41 ), which was also observed in recent studies ( 42 – 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reached inconsistent conclusions on the correlation between TL and hypertension. For instance, some previous studies suggested that there was no association between TL and blood pressure ( 38 40 ). A previous meta-analysis of 10 studies indicated a significant negative correlation between TL and hypertension ( 41 ), which was also observed in recent studies ( 42 – 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown, that telomeres length stronger associated with the pace of aging and age-related homeostatic dysregulation, than different panels of epigenetic clocks, including the 353-CpG clock, so telomeres length associated with some unique aspects of aging unrelated to other biomarkers [15]. Other authors believe that leukocyte telomere lengths are associated with oxidative stress and inflammation even in healthy people [16], which indicates that systemic oxidative stress and inflammation are associated with the increased risk of cardiovascular disease and may accelerate telomere shortening, thereby mitigating the effects of the hereditary component of TL [17]. In addition, considering the systemic effects of oxidative stress, inflammation, and the similar indicators of shortening of TL in somatic tissues [2], the rate of the shortening of TL in the blood cells reflects this in the vascular tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Also these studies included few oxidative stress parameters that were measured after telomere shortening had already occurred, i.e. not in the period between the baseline and the subsequent growth of telomeres [17,19,20]. In this regard, it can be concluded that the role of oxidative stress in telomere shortening in vivo is currently unclear, and more extensive studies are required.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, some CVD risk factors were associated with telomere length, such as obesity, plasma lipids, or hypertension. These associations could be influenced by the age of examined subjects and generally showed strong heterogeneity effects [ 129 , 130 , 131 ].…”
Section: Telomeresmentioning
confidence: 99%